You are on page 1of 3

# Simultaneous equations

1. 2x + 5y = 24
4x + 3y = 20
The first step would be to make one of the
variables have the same coefficient in both
equations. If we multiply the first equation
by 2, this would make the coefficients of x
the same in both equations.
4x + 10y = 48 (multiplied by 2)
4x + 3y = 20 (stays the same)
Now that the coefficient of x in both
equations are the same, we can now
eliminate the x by subtracting these
equations.
7y = 28
Solving for y we get:

2. 3x + 2y = 19
x + 8y = 21
The first step would be to make one of the
variables have the same coefficient in both
equations. If we multiply the second
equation by 3, this would make the
coefficients of x the same in both
equations.
3x + 2y = 19 (stays the same)
3x + 24y = 63 (multiplied by 3)
Now that the coefficient of x in both
equations are the same, we can now
eliminate the x by subtracting these
equations.
-22y = -44
Solving for y we get:

y=4
Now we take this value for y and
substitute it into either of the two original
equations.
So, if we sub it into the first equation we
see that:
2x + 5y = 24
2x + 5(4) = 24

y=2
Now we take this value for y and
substitute it into either of the two original
equations.
So, if we sub it into the first equation we
see that:
3x + 2y = 19

2x = 4

3x + 2(2) = 19

x=2

3x = 15

## So our values are x = 2 and y =4.

x=5
So our values are x =5 and y =2.

3. 3x - y = 9
4x - y = -14
In this equation, the values in front of y
are the same. So we do not have to
multiply these equations by any values.
We can go ahead and subtract these
equations to eliminate the y (beware that
you do not add these equations as this will
not eliminate the y).
-x = 23
x = -23
Now we take this value for x and
substitute it into either of the two original
equations.
So, if we sub it into the first equation we
see that:

## Now that the coefficient of y in both

equations are the same, we can now
eliminate the y by subtracting these
equations.
13x = 13
Solving for y we get:
x= 1
Now we take this value for x and
substitute it into either of the two original
equations.
So, if we sub it into the first equation we
see that:
7x + 5y = 32
7(1)+ 5y =32
5y = 25

3x y = 9

y=5

3(-23) y = 9
-69 y = 9
-y = 78
y = -78
So our values are x =-23 and y =-78.
4. 7x + 5y = 32
3x + 4y = 23
The first step would be to make one of the
variables have the same coefficient in both
equations. In this case we have to multiply
both equations in order to make any of the
two variables the same. If we want to
make the y values the same, we multiply
the first equation by 4 and the second by
5. This will make both y variables have a
coefficient of 20.
28x + 20y = 128 (multiplied by 4)
15x + 20y = 115 (multiplied by 5)

## So our values are x = 1 and y =5.

5. 3x - 2y = 7
4x + y = 13
The first step would be to make one of the
variables have the same coefficient in both
equations. In this case we can multiply the
second equation by two to make the
coefficient of y in the second equation the
same as that in the first (ignore the
minus).
3x - 2y = 7 (stays the same)
8x + 2y = 26 (multiplied by 2)
Now that the coefficient of y in both
equations are the same, we can now
eliminate the y by adding these equations.
11x = 33
Solving for y we get:
x= 3

## Now we take this value for x and

substitute it into either of the two original
equations.

2x +7y= 17
2x + 7(3)=17
2x = -4

## So, if we sub it into the first equation we

see that:
3x - 2y = 7
3(3)- 2y =7
-2y = -2
y=1
So our values are x = 3 and y =1.
6. 2x + 7y = 17
5x + 3y = -1
The first step would be to make one of the
variables have the same coefficient in both
equations. In this case we have to multiply
both equations to make one of the
variables have the same coefficient. If we
want to make the coefficients of x to be
the same, we multiply the first equation by
5 and the second equation by 2.
10x + 35y = 85
10x + 6y = -2
Now that the coefficient of x in both
equations are the same, we can now
eliminate the x by subtracting these
equations.
29y = 87
Solving for y we get:
y= 3
Now we take this value for y and
substitute it into either of the two original
equations.
So, if we sub it into the first equation we
see that:

x = -2
So our values are x = -2 and y =3.
7. 4x - 0.5y = 12,5
3x + 0.8y = 8,2
The first step would be to make one of the
variables have the same coefficient in both
equations. In this case we can multiply the
first equation by 3 and the second
equation by 4 to make the coefficients of x
the same.
12x -1.5y = 37,5 (multiplied by 3)
12x + 3.2y= 32,8 (multiplied by 4)
Now that the coefficient of x in both
equations are the same, we can now
eliminate the x by subtracting these
equations.
-4.7x = 4,7
Solving for y we get:
x= -1
Now we take this value for x and
substitute it into either of the two original
equations.
So, if we sub it into the first equation we
see that:
4x 0.5y = 12,5
4(-1) 0.5y = 12,5
-0.5y = 16,5
y = -33.
So our values are x = -1 and y =-33.